2023
DOI: 10.3390/electronics12030564
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Design of Inductive Transmitter and Receiver Coils for Wireless Power Transmission

Abstract: Wireless power transmission (WPT) is commonly used today in many important daily applications, such as electric vehicles, mobile phones, and implanted medical devices. The transmitter and receiver coils are essential elements in the WPT system, and the coupling coefficient between these coils plays an important role in increasing the power transfer efficiency. In this work, we introduce a new approach to optimizing the coupling coefficient between the transmitter and the receiver coils by changing the geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…By substituting Equation (10) into Equation ( 8), the M a1b1 of the N m -th turn of the mosquito coil can be obtained as follows:…”
Section: Mutual Inductance Calculation Of Combined Coilsmentioning
confidence: 99%
See 1 more Smart Citation
“…By substituting Equation (10) into Equation ( 8), the M a1b1 of the N m -th turn of the mosquito coil can be obtained as follows:…”
Section: Mutual Inductance Calculation Of Combined Coilsmentioning
confidence: 99%
“…This displacement leads to changes in the IPT system's mutual inductance [9], affecting both the output power and transmission efficiency. Consequently, it is crucial to prioritize the investigation of the coil structure design and parameter optimization for the coupling mechanism in order to enhance the IPT system's anti-misalignment performance [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that it was better to accept the skin effect than to reduce the wire diameter for the low-power WPT estimation. An equivalent circuit was also proposed, represented by a single WPT cell, which yielded a simpler and faster solution for a periodic distribution of low-power circular planar coils and square planar coils [13]. Nahed et al [14] investigated the application of quasi-elliptic curves in designing the transmitter and receiver coils of WPT circuits.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of science and technology, inductive power transfer (IPT) technology has attracted more and more attention. Compared with the traditional charging method, this technology is safe, reliable, flexible and convenient, and has strong adaptability [1][2][3][4][5][6]. As a new type of power supply, it is widely used in electric vehicle charging [7], electronic products charging [8], biomedical [9] and underwater vehicle fields [10], as well as other fields.…”
Section: Introductionmentioning
confidence: 99%